STRATEGI PENINGKATAN AKUNTABILITAS KINERJA INSTANSI PEMERINTAH: Studi pada Inspektorat Kabupaten Temanggung - Meidi Syaflan; Eny Sulistiarini (Jurnal Riset Akuntansi dan Bisnis Indonesia STIE Widya Wiwaha, 2022)
The results of the evaluation of the performance accountability system of the Inspectorate Temanggung Regency have not been optimal. The research method used in this study is the Qualitative Research Method, which is descriptive analysis in the form of written or spoken words from the observed behavior, while the purpose of this study is to analyze what factors cause the accountability of the performance of Inspectorate Temanggung Regency not to comply with targets set and to formulate efforts to improve the performance of Inspectorate Temanggung Regency. The factors that cause the accountability of the performance of the Temanggung Regency is not optimal, namely the review of the Main Performance Indicators and the Renstra Review has not been carried out routinely, the report on the action plan has not been available, rewards and punishments have not been applied in achieving performance and reporting performance, and performance measurement has not used technology. information. Efforts that must be made by Inspectorate Temanggung Regency in increasing the value of SAKIP, namely Inspectorate Temanggung Regency must review the Main Performance Indicators and Review the Renstra Document of Inspectorate Temanggung Regency for 2019-2023, the Action plan that has been made by Inspectorate Temanggung Regency must be followed up with a report on the implementation of the plan Actions, rewards and punishments should be given to employees who have achieved good performance and reported performance and performance measurement should use information technology.